1989
DOI: 10.4278/0890-1171-4.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Data for State Health Departments: Telephone versus in-Person Survey Estimates of Smoking and Alcohol Use

Abstract: During 1988, more than 40 state health departments conducted telephone surveys to obtain state-specific population estimates of the prevalence of adult health behaviors and health practices. However, the comparability of estimates obtained from these telephone surveys with more expensive in-person surveys has not been assessed in an applied setting. This study compared the prevalence estimates of smoking and binge drinking obtained from a telephone survey (N = 1,492) with an in-person survey (N = 2,802) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In other contexts, smokers tend to underreport their smoking practices (16), and are more easily lost to followup than nonsmokers (35). However, age-and sex-specific prevalence estimates of smoking are reported to be similar for telephone and in-person surveys (36). A comparison of our control subjects with population-based sex-, age-, and education-specific smoking prevalence rates (37) showed that our control subjects were more often smokers, arguing against both information and selection bias.…”
Section: Discussionmentioning
confidence: 45%
“…In other contexts, smokers tend to underreport their smoking practices (16), and are more easily lost to followup than nonsmokers (35). However, age-and sex-specific prevalence estimates of smoking are reported to be similar for telephone and in-person surveys (36). A comparison of our control subjects with population-based sex-, age-, and education-specific smoking prevalence rates (37) showed that our control subjects were more often smokers, arguing against both information and selection bias.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, although the NIAAA guidelines recommend a 2‐hour period of time to reflect a binge‐drinking episode, the BRFSS items specify only that the five (for men) or four (for women) drinks were consumed on a single occasion. However, the BRFSS items used to assess alcohol use have been found to produce prevalence estimates that are comparable to other national surveys 43 and methodologies, such as in‐person interview 44 . Finally, the item to assess drinking and driving ( “During the past 30 days , how many times have you driven when you’ve had perhaps too much to drink?” ) is vague and highly subjective, which could have adversely affected the accuracy of the reports relative to other measures of drinking and driving which specify number of drinks or use biochemical measures of blood alcohol content.…”
Section: Discussionmentioning
confidence: 96%
“…At least 2 studies have assessed the reliability of BRFSS alcohol use measures based on reinterview methods (Stein et al, 1993(Stein et al, , 1995. At least 5 studies have assessed the validity of BRFSS alcohol use measures, based on either correlations between self-reported alcohol use and alcohol sales data (Smith et al, 1990), comparisons with household interviews (Anda et al, 1989;Bradstock et al, 1985;Gentry et al, 1985), or comparisons between alternative versions of BRFSS questions (Serdula et al, 1999). A comprehensive review of these studies concluded that the reliability of the BRFSS questions on alcohol consumption and binge drinking is high while the validity is fair; that BRFSS data underestimate the prevalence of heavier drinkers; and that the validity of the alcohol-impaired driving question is unknown (Nelson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%